Parasitoid virus-like particles destroy Drosophila cellular immunity. - Rizki, R M (1990)
Parasitoid wasps must avoid the destructive effects of the host's cellular defense system in order to exploit the host hemocoel as a suitable environment for their survival. To protect their eggs from encapsulation by Drosophila melanogaster blood cells, Leptopilina heterotoma females inject a factor that selectively destroys lamellocytes, the type of Drosophila blood cell involved in recognition and encapsulation of large foreign objects. Other types of host blood cells, including the phagocytic plasmatocytes, remain functional. This report demonstrates that the destructive factor for lamellocytes is a virus-like particle (VLP) stored in the reservoir of an accessory gland associated with the female wasp reproductive system. We show that VLPs enter Drosophila blood cells in vitro. VLPs are found free in the cytoplasm of lamellocytes but are confined to phagocytic vesicles of plasmatocytes. As lamellocytes are susceptible to the VLP infection and plasmatocytes are not, we conclude that the mode of VLP entry and its disposition in the cytoplasm determine the fate of the infected host blood cell.